ANALISIS EFEKTIVITAS PROGRAM REVITALISASI PASAR TRADISIONAL DAN DAMPAKNYA TERHADAP PENDAPATAN PEDAGANG DAN PENGELOLAAN PASAR POHGADING - Cyntia Pratiwi, Kadek; Kartika, I Nengah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The purpose of this study is to find out: 1). The level of effectiveness of the market revitalization program in the Pohgading market in North Denpasar District, 2). The income conditions of traders before and after the traditional market revitalization program in the Pohgading market in North Denpasar District, 3). Market management conditions before and after the traditional market revitalization program in the Pohgading market in North Denpasar District. This research was conducted at the Pasar Pakraman Pohgading Village, North Denpasar District. The analysis technique used is description analysis and different test two paired sample averages. Based on the analysis, it can be concluded that the success rate of the traditional market revitalization program is quite effective seen from the input variable effectiveness level of 73.25 (quite effective), the process variable effectiveness level is 67.25 (quite effective) and the output variable is 72 , 75 (quite effective). There is an increase in merchant income after the implementation of a traditional market revitalization program. Better market management after traditional market revitalization programs.